Effects of salt stress on rice growth, development characteristics, and the regulating ways: A review - Sajid Hussain; Jun-hua ZHANG; Chu ZHONG; Lian-feng ZHU; Xiao-chuang CAO; Sheng-miao YU; James Allen Bohr; Ji-jie HU; Qian-yu JIN (Journal of Integrative Agriculture, 2017)
Rice (Oryza sativa L.) is highly susceptible to the rhizosphere salinity than other cereals. High sensitivity has been observed, mainly at vegetative and reproductive stages in rice. It is the duty of plant physiologists to comprehend the growth, development, and physiological processes of rice plants under stress. This paper includes the overview of rice growth and developmental processes influenced by salt stress and the regulation pathways involved in these processes. It also includes the promising salt tolerance strategies, i.e., genetic modification techniques, agronomic practices to improve rice growth, yield, and role of phytohormones and their management, especially inhibition of ethylene biosynthesis by using inhibitors 1-methylcyclopropene (1-MCP). Rice cultivation may be a first choice for improvement of salt tolerance through plant growth regulators and improved cultivation techniques. This study will significantly improve the understanding toward low rice grain yield and poor rice resistance under salt stress and will also stream scientific knowledge for effective utilization of salt affected soils by using different regulating ways.